Pengaruh Motivasi Kerja, Kompetensi dan Disiplin Kerja terhadap Kinerja Guru SMA Warga Surakarta - Aliffia Ori Enjarwati; Riska Fii Ahsani (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Human resources are an important factor in an organization or company. In order to achieve company goals, human resources must have a high level of performance to drive success and achieve company goals. Factors that can influence performance are motivation, competence and work discipline. The formulation of the problem in this research is whether work motivation, competence, work discipline have a significant effect on the performance of Surakarta Warga Senior High School teachers. This research aims to analyze the significance of the influence of work motivation, competence, work discipline on the performance of Surakarta Warga Senior High School teachers. This research uses a survey method conducted on Surakarta Citizen High School teachers. Data collection in this research used a questionnaire distributed to Surakarta Warga Senior High School teacher respondents. The population in this study were all Surakarta Warga Senior High School teachers, totaling 43 teachers. The samples in this research were 43 using the sensul method or saturated samples. The research uses instrument tests and classical assumption tests. The data analysis technique used in this research uses descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination (R2). The statistical test results show that the test instruments for all variables are valid and reliable. The results of the classical assumption test show that all variables pass the classical assumption test. The results of this research show that partially and simultaneously work motivation, competence and work discipline have a significant effect on the performance of Surakarta Warga Senior High School teachers. For further research, it is hoped that researchers can use other variables not examined in this research and use other research models.